The Role of Independent Work in the Training of Psychologists in Institutions of Higher Education - Valentyn Vovk (Pedagogical Discourse, 2023)
The article analyzes the theoretical aspects of the role of independent work in the process of training psychologists. The analysis of scientific sources made it possible to clarify the essence and content of the main concepts of the defined problem, namely: «independent work», «self-education», «professional training», «independent creative activity». The article also clarified that the concept of «independent work» is defined as a type of educational activity aimed at forming the cognitive abilities and interests of the future psychologist, its focus on continuous self-education. Independent work of students is an important component in training a psychologist as a highly qualified, competitive specialist capable of competent professional psychological activity in modern conditions at the level of world standards. Using the author's questionnaire to determine the quality of the organization of students' independent work, it was established: what is the incentive for them to perform independent work, what difficulties do they encounter during its implementation, how systematically during the semester do they perform the tasks of independent work, what are the methods of pedagogical stimulation of performance independent work they like the most, how often do students turn to the teacher for help in performing independent work, what would they like to have in order to improve the quality of the organization of independent work, are students familiar with the criteria for evaluating the performance of independent work tasks and how often do they visit the educational library institution and city library.